Best age for surgery for infantile esotropia - Simonsz, Huibert J.; Kolling, Gerold (European journal of paediatric neurology, 2011)
Infantile esotropia (IE) is defined as an esotropia before the age of 6 months, with a large angle, latent nystagmus, dissociated vertical deviation, limitation of abduction, and reduced binocular vision, without neurological disorder. Prematurity, low birth weight, and low Apgar scores are significant risk factors for IE. US standard age of first surgery is 12-18 months, in Europe 2-3 years. The only study to date with prospectively assigned early- and late-surgery groups and evaluation according to intention-to-treat, was the European Early vs. Late Infantile Strabismus Surgery Study (ELISSS). In that study 13.5% of children operated around 20 months vs. 3.9% (P = 0.001) of those operated around 49 months had gross stereopsis (Titmus Housefly) at age 6. The reoperation rate was 28.7% in children operated early vs. 24.6% in those operated late. Unexpectedly, 8% in the early group vs. 20% in the late group had not been operated at age 6, although all had been eligible for surgery at baseline at 11 SD 3.7 months. In most of these children the angle of strabismus decreased spontaneously. In a meta-regression analysis of the ELISSS and 12 other studies we found that reoperation rates were 60-80% for children first operated around age 1 and 25% for children operated around age 4. Based on these findings, the endpoints to consider when contemplating best age for surgery in an individual child with IE should be: (1) degree of binocular vision restored or retained, (2) postoperative angle and long-term stability of the angle and (3) number of operations needed or chance of spontaneous regression. IE is characterized by lack of binocular connections in the visual cortex that cannot develop, e.g. because the eyes squint, or do not develop, e.g. after perinatal hypoxia. As the cause of IE, whether motor or sensory, is a determinant of surgical outcome, a subdivision of IE according to cause is needed. As similarities exist between IE and cerebral palsy we propose to adapt the working definition formulated by the Surveillance of Cerebral Palsy in Europe and define IE as “a group of permanent, but not unchanging, disorders with strabismus and disability of fusional vergence and binocular vision, due to a nonprogressive interference, lesion, or maldevelopment of the immature brain, the orbit, the eyes, or its muscles, that can be differentiated according to location, extent, and timing of the period of development.”